Decontamination of Cr(VI) by graphene oxide@TiO2 in an aerobic atmosphere: effects of pH, ferric ions, inorganic anions, and formate. Issue 8 (2nd March 2018) - Hu, Xinjiang; Zhao, Yunlin; Wang, Hui; Cai, Xiaoxi; Hu, Xi; Tang, Chunfang; Liu, Yunguo; Yang, Yuanxiu
Abstract: BACKGROUND: In this study, a graphene oxide@TiO2 composite (GO/TiO2 ) was prepared and characterized by SEM, EDX, XRD, nitrogen adsorption–desorption isotherm, and XPS. Photocatalytic reduction and removal of Cr(VI) using this composite in an aerobic atmosphere were studied under UV irradiation. The effects of pH, ferric ions, inorganic anions, and formate were investigated systematically. RESULTS: The Cr(VI) reduction rate decreased with increasing solution pH. The presence of ferric ions in the system improved the photocatalytic reduction process. The effects of SO4 2− and PO4 3− on the process were higher than those of Cl − and NO3 − . Formate slightly inhibited adsorption of Cr(VI), while it improved Cr(VI) reduction. GO/TiO2 has good stability and it maintained full photoreduction activity for at least three cycles. CONCLUSION: The results indicated that GO/TiO2 can thermodynamically reduce Cr(VI) to Cr(III) under UV light. Environmental conditions and wastewater characteristics (e.g. pH, ferric ions, inorganic anions, and formate) can influence the decontamination process because they affect the interactions between chromium ions and GO/TiO2 and alter the electron‐transfer pathways. The results suggest that the GO/TiO2 is an attractive material for removing hexavalent chromium from water using a photocatalytic process. © 2018 Society of Chemical Industry